PORTRAYING TEACHERS' STRATEGIES TO TEACH ENGLISH IN THE LEARNING-FROM-HOME MODEL - Farouk Imam Arrasyid (Universitas Wiralodra, 2023)
This study examines teachers' strategies as the learning process transitions from face-to-face to online learning. In other words, the researcher is attempting to investigate strategies for piquing students' interest in English learning at home. The qualitative research methodology was utilized for this investigation. The researcher used three methods to conduct this study: observation, interviewing participants, and keeping detailed records. Methods of qualitative data analysis were applied in this particular research project. The subject of this research is the seventh-grade teacher and students at SMPN 1 Sumber Cirebon. This data revealed that using appropriate learning media not only facilitates the delivery of material but also increases effectiveness in achieving learning goals, which can increase interest and motivation to learn. As a result, the accuracy of selecting learning media is determined not by price but rather by the level of efficiency and effectiveness in achieving goals. Students' individual interests had the greatest influence on their career goals, and thus course selections in a well-prepared online classroom would result in successful learning and teaching. This study highlights opportunities for educators, technology developers, curriculum designers, administrators, policymakers, researchers, and academics to enhance online learning experiences, student engagement, and teaching practices.